In vitro evaluation of poly-ε-caprolactone-hydroxypatite-alumina electrospun fibers on the fibroblast’s proliferation - Reyes-López, Simón Yobanny (2020)
A biomaterial can replace the function of a real organ, conferring properties of support, regeneration or resistance. In the present investigation, a new composite was developed in the form of a polymeric membrane embedded with hydroxyapatite and alumina particles to be used as scaffolding and to allow cell viability. The support matrix is poly ε-caprolactone, which is a biodegradable polymer, hydroxyapatite is the ceramic that contributes to the improvement of osteoconductive and osteo-regenerative properties, while alumina provides the hardness to the composite for its viable application in the orthopedic industry. The morphology of the composite resulted in an interweaving of fibers with a diameter of 840 ​± ​230 ​nm. The composites were analyzed to the MTT cytotoxicity test, showing that none of the composites were toxic (p ​= ​0.0001); where the PCL/HA/α-Al2O3 composite showed greater cellular viability with 238%, demonstrating its possible usefulness as orthopedic material, in filling fractures, or bone imperfections caused by physical damage.